(untitled) (Shaheed Smriti Journal, 2025)
The Siege of Krishnapur (1973) by J. G. Farrell is a fictional and symbolically real depiction of Indian resistance against British colonialism during the Sepoy Mutiny of 1857. The novel is fabricated in colonial historiography that analyses how it reflects the military resistance and the ideological clash between colonizers and the colonized. The 1857 revolt represented by British colonizers as a mere mutiny that is reinterpreted here as a foundational act of Indian nationalism and anti-imperial struggle. This paper has analyzed how Indians demonstrated the resistance against British imperialism in Sepoy mutiny 1857 in relation to their freedom, justice, and rights; how they fought against the atrocity of the colonizers. This study is based on a qualitative, historical research design to explore the resistance of the sepoys portrayed during that time within the broader context of the 1857 Sepoy Mutiny. To accomplish this research, I have used books and journal articles as the secondary data on the locale of the sepoy mutiny 1857 in relation to the portrayal of Indian society and their dominated voices, the contradictory perceptions of Indian civilization and colonizers’ barbarism often used to justify colonial dominance. The result of this study is significant in the sense that it has presented the power dynamics of the colonizer and the colonized.